A field study of management and husbandry factors affecting reproductive performance of dairy cows in Malacca, Malaysia - Manefield, Geoffrey W. (1985)
The problem of poor reproductive performance and lack of profit from smallholders' dairy cows in Malacca was addressed . during the period July 1981 to May 1983. Performance of 290 cows on 82 farms with varying feeding and management regimes were studied over a period of at least one year. Performance history and physical examination of the cows at repetitive visits provided data which was analysed for .significant differences (P < 0.05) in productive and reproductive performance against variations in husbandry, and population characteristics of cows and farmers. Increasing parity from one to three or greater decreased calving to conception interval mean by 4.2, median by 5.5 and for 90% of cows pregnant by 5.6 months at a level of feeding 0.5 NRC recommendations. With full feeding the corresponding figures were 1.8, 1.7 and 2.1 (but between parity one and two 2.7, 3.0 and 4.9). Parity exerted its greatest effect between parity one and two. No increase in (milk) production peak occurred with increase in parity. Increase in feeding level from 0.5 to full NRC recommendations decreased calving to conception interval mean for parities one, two and three with three plus by 3.2, 2.8 and 0.8 months, median by 4.0, 1.8 and 0.2 and for 90% of cows pregnant by 10.7, 9.8 and 7.2. Greatest effect of full feeding on reproductive performance was reduction of a less fertile tail. Field data suggests that the increase to full feeding level would result in a milk production increase of 146% for the poorly fed cows. Of this 18% would be due to improved reproduction, 50% to increase in production peak and 32% to decrease in dry period (from 7.5 to 1.8 months). The calculations are supported by field observations. Reproductive performance was unaffected by oestrus detection method and A.I. versus natural mating. Maximum production peak and best reproductive performance was associated with optimum body condition. Under cost/price conditi6ns prevailing, effective extension of the facts established was able to achieve profit levels which exceeded planned targets.